Philosophy of Science in Islamic Tradition: Implications for Modern Interdisciplinary Research and Knowledge Production - Eka Nada Shofa Alkhajar; Firdaus Firdaus (Harmony Philosophy: International Journal of Islamic Religious Studies and Sharia, 2024)
This paper explores the contributions of classical Islamic philosophy of science to the modern interdisciplinary research landscape. The study focuses on how key philosophical principles such as the concept of ‘ilm al-tawḥīdī (unity of knowledge) and the integration of ethics and spirituality can enhance contemporary research methodologies. Islamic philosophy advocates for a holistic approach that bridges the gap between empirical science and metaphysical insights, promoting a unified view of knowledge that incorporates not only rational and empirical elements but also ethical and spiritual dimensions. The paper discusses how Islamic ethical frameworks, such as Adab al-‘ilm (ethics of knowledge), can influence modern research by emphasizing responsibility, integrity, and the interconnectedness of all forms of knowledge. Additionally, the study highlights the potential for integrating Islamic epistemology into interdisciplinary research, fostering more inclusive, responsible, and ethically grounded scientific practices. The integration of both Islamic and secular research models is proposed as a way to create a more robust and sustainable research framework that values both scientific rigor and ethical responsibility. The paper also addresses the challenges of reconciling Islamic principles with secular academic frameworks, suggesting future research avenues to develop systematic methodologies that integrate Islamic ethical and epistemological values with modern scientific practices. In conclusion, the paper emphasizes the importance of incorporating both spiritual and empirical insights in modern research to address complex global challenges in a more comprehensive and ethically grounded manner.